2021
DOI: 10.3390/en14113358
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Calendar Aging Behavior of Six Different Lithium-Ion Cell Chemistries in Terms of Parameter Variation

Abstract: The degradation of lithium-ion cells is an important aspect, not only for quality management, but also for the customer of the application like, e.g., scooters or electric vehicles. During the lifetime of the system, the overall health on the battery plays a key role in its depreciation. Therefore, it is necessary to monitor the health of the battery during operation, i.e., cycle life, but also during stationary conditions, i.e., calendar aging. In this work, the degradation due to calendar aging is analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Geisbauer et al conducted a comparative study on the calendar aging behavior of five different cathode materials by relating the capacity decay to the resistance increase of full cells. It is found that NMC and NCA show a great resistance increase at high temperature and SOC, while LFP exhibits the best stability with little resistance increase at different conditions . Keil et al also studied the impacts of SOC and temperature on the calendar aging of three kinds of commercial LIBs with NMC, NCA, and LFP cathodes .…”
Section: Application Of Eis To Lib’s Aging Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Geisbauer et al conducted a comparative study on the calendar aging behavior of five different cathode materials by relating the capacity decay to the resistance increase of full cells. It is found that NMC and NCA show a great resistance increase at high temperature and SOC, while LFP exhibits the best stability with little resistance increase at different conditions . Keil et al also studied the impacts of SOC and temperature on the calendar aging of three kinds of commercial LIBs with NMC, NCA, and LFP cathodes .…”
Section: Application Of Eis To Lib’s Aging Studymentioning
confidence: 99%
“…It is found that NMC and NCA show a great resistance increase at high temperature and SOC, while LFP exhibits the best stability with little resistance increase at different conditions. 113 Keil et al also studied the impacts of SOC and temperature on the calendar aging of three kinds of commercial LIBs with NMC, NCA, and LFP cathodes. 114 As shown in Figure 6c, the internal resistance of NMC and NCA increases slowly at low SOC (<60%) but rapidly enhances at high SOC, while the resistance of LFP shows little variation at different SOC.…”
Section: Eis Variations At Different Aging Conditionsmentioning
confidence: 99%
“…The main technological challenge is connected with the reliability and safety of the most important components of electric vehicles: batteries, power electric convertors and electric motors [21]. A crucial question here is the battery technology and lifecycle [22][23][24][25], but environmental aspects of their production and recycling cannot be forgotten either [26,27]. From the point of view of electric transport functioning, a critical issue is the charging infrastructure [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent studies conducted by Geisbauer et al, proved that despite Li-ion technology offering a wide range of chemistries, such as Nickle Manganese Cobalt Oxide (NMC), Nickle Cobalt Aluminum Oxide (NCA), Lithium Titanium Oxide (LTO), Lithium Cobalt Oxide (LCO) or Lithium Iron Phosphate (LFP), none of them were able to avoid the calendar ageing 7 . The study also clearly demonstrated high temperatures lead to even higher degradations 7 . These factors are important because, e.g.…”
Section: Introductionmentioning
confidence: 99%